Urinary catheterization 2: technique and managing failure. (2nd September 2019) - Tan, Elizabeth; Ahluwalia, Aashish; Kankam, Hadyn; Menezes, Pravin
Abstract : Urinary catheterization is an important procedure that is regularly performed in hospital. All clinicians should have a good working knowledge of urinary catheters and the competence to manage them effectively. This topic is discussed over two articles: the first article focused on indications, and this second discusses techniques and managing failure. Good technique is essential to prevent complications and if problems do occur, these must be managed efficiently to prevent long-term consequences. In some situations, this may require referral to the urology team for more specialized intervention. This article discusses this in more detail to help guide clinicians involved in urethral catheterization.